Evaluation of a novel approach to measuring well-being in the workplace - Juniper, Bridget (Cranfield University, 2010)
The well-being of employees is an important issue. Researchers, policy makers and organisations are directing more resource into this field as the link between the health of people and their performance in the workplace becomes increasingly understood. This research programme examines how employee well-being can be measured. Having the right tools to successfully appraise well-being at the outset is judged to be imperative where any research or organisational programme to bring about change is under consideration. A review of existing methods indicates that the current provision of scales to assess the well-being of workers is limited and the construction techniques used in their development may be improved upon. At the core of this study is the testing of a new measurement framework which seeks to address these deficiencies. This innovative approach is taken from one established practice used to assess the well-being of patients using health related quality of life instruments. Three organisations participated in the study; a call centre operation, a police force and a county-based library service. Using qualitative and quantitative methodologies, three pilot questionnaires were constructed using Impact Analysis; an established procedure deployed in health related quality of life settings. Basic findings from each case study were analysed against conventional construction methods and against existing employee well-being scales. Results were also examined in respect of how they compared with the wider literature on employee well-being. ii The Impact Analysis method was critically appraised. Although weaknesses in respect of some of the qualitative phases of analyes were noted, the overall notion of transferring the practice of Impact Analysis to an occupational setting was assessed as cautiously encouraging. While this scale construction method lacks the statistical elegance of factor analytical methods, provisional indications suggest potential benefits in content validity over extant occupational scales where the assessment of a study population’s own experiences are critical to any well-being evaluation strategy. Based on the findings, a new operational definition for employee well-being is posited. A new, working model is also proposed. This emphasises for the first time, the need for specificity when researchers and organisations are seeking to evaluate a multi-dimensional, subjective construct that is employee well-being. Limitations regarding the study are noted. This means that the findings should be treated as tentative rather than conclusive. Nevertheless, it is hoped that this study will inject new thinking on how employee well-being may be evaluated using an alternative approach. By doing so, it is ventured that research communities and employers alike may take up the methods described in this study to conduct assessment programmes that could benefit not just the study teams or the employers, but importantly, the workers themselves.
Keywords: well-being; employee; measurement; health; evaluation; quality of life; assessment; quality of work life